Perceptions on Knowledge Transfer Effectiveness in Multinational Corporations within the Renewable Energy Industry in South Africa - Phiri, Asante (University of the Witwatersrand, Johannesburg, 2022)
The purpose of this quantitative study was to examine how employees working in multinational companies in the South African renewable energy industry, specifically those working for companies participating in the Renewable Energy Independent Power Producer Programme (REIPPP), experience and perceive the knowledge transfer initiatives of their companies and the effectiveness thereof. The REIPPP has a strong prevalence of multinational companies and one of its goals is the transfer of skills. With the application of knowledge identified as a precursor to the development of skill and multinational companies identified as vehicles for knowledge transfer, the study investigates the effectiveness of knowledge transfer within the REIPPP. A survey questionnaire was used to assess the degree to which the elements identified by seminal models and as critical success factors for knowledge transfer were applied by multinational companies in the renewable energy industry in South Africa. Exploratory statistics techniques and regression analysis was used to identify relationships and verify expected relationships between critical factors and the benefits of as well as satisfaction with knowledge transfer. The findings indicate that multinational companies within the REIPPP apply the knowledge transfer practices aligned with the critical success factor identified in knowledge transfer literature. Respondents predominantly had positive views of all aspects of the strategies, processes and systems used in the transfer of knowledge. Most respondents were satisfied with and identified the benefits of their company’s knowledge transfer initiatives, 65.98% and 69.01% respectively. Critical success factors that negatively affect knowledge transfer were found to be largely overcome within the industry resulting in negligible effect on the satisfaction with and benefits of transfer. Potential areas for improvement were identified based on analysis of respondent responses. Improvement areas include the periodic assessment of knowledge transfer program effectiveness by multinational companies, as well as the encouragement and monitoring of transfer effectiveness by government programme sponsor
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2022
Keywords: knowledge transfer; multinational; critical success factors; REIPPP; UCTD; SDG-7: Affordable and clean energy